Sonographic differentiation between lymphatic and metastatic diseases in cervical lymphadenopathy. (22nd August 2017) - Strassen, Ulrich; Geisweid, Christina; Hofauer, Benedikt; Knopf, Andreas
Abstract : Objectives/Hypothesis: The spectrum of differential diagnosis in cervical lymphadenopathy is extremely broad. In lymphoma and inflammatory diseases, surgical approaches are restricted to diagnostic lymph extirpation, whereas metastatic outgrowth into regional lymph nodes usually requires neck dissection. Lymph node surgery has to manage the balancing act between sufficient radicality and preservation of functional structures. The current study, therefore, aimed to identify parameters to differentiate between lymph nodes of lymphatic and metastatic origin. Study Design: Single‐center, retrospective cohort study. Methods: Clinical and sonographic parameters from all patients who underwent diagnostic cervical lymphadenectomy from 2010 to 2015 (N = 262) were included in this retrospective analysis. Parameters with significant differences between the two subgroups were utilized to create a clinical algorithm to distinguish between cervical lymphadenopathy of lymphatic and metastatic genesis. Results: Statistically significant differences between the two subgroups could be shown for clinical (gender, age, nicotine/alcohol abuse, B symptoms, history of cutaneous melanoma, or lymphoma) and ultrasonographic parameters (string‐of‐beads confirmation, bilaterality, homogenous echostructure, localization in level I, long‐to‐short axis ratio, and hilar vascularity). The proposed algorithm yielded a sensitivity of 92.4% for metastatic disease. Conclusions: The implemented algorithm based on ultrasonographic and clinical criteria contributes to one‐step surgical approaches that guarantee a sufficient radicality with a minimum of functional loss. Level of Evidence: 4. Laryngoscope, 128:859–863, 2018